Social Stratification of Ghanaian English: The Case of RP Dental Fricatives /θ/ and /d/ - Aziaku, Lena Awoonor- (International Journal of Publication and Social Studies, 2017)
This paper is a socio-phonetic study of two RP phonemes /θ/ and /ð/ produced by sixty participants from a relatively homogenous Akan speaking communities in Ghana. It takes into consideration levels of formality and speakers’ socio-educational backgrounds. Adopting both qualitative and quantitative methods for the data sampling and analysis, the paper attempts to probe the general perception that non-native speakers of English constantly substitute the features of their first language (L1) for second language (L2) features. Yankson (1971), for example, believes that this phenomenon is due to lack of L2 features in the L1; ‘any L2 sounds that a Ghanaian English lacks, are non-existent in Ghanaian language'. Some writers therefore posit that the lack of L2 features in the L1 poses learning difficulties for L2 acquisition. The general view, therefore, is that a leaner of English will always differ linguistically from a native English speaker. The result of this study partially corroborates this general view. For example, there has been a substitution of the stops [t], [th], [d], [d̪], and the labiodental fricative [f], for the RP /θ/ and /ð/. Nevertheless, the use of the standard variants, [θ] and [ð], by the speakers for the RP /θ/ and /ð/, and the fact that the choice of these variants is significantly influenced by the socio-educational backgrounds of the speakers, suggest that these previous researches are deficient in methodology; and therefore lack objectivity. This paper thus provides a methodological framework which will help address the lack of objectivity and deficiency in methodology of researches on non-native English speakers. Also, sustainable empirical studies are needed to lead us into more perspectives on Ghanaian English phonological variation.